The Bangladesh Midwifery Programme a giant step towards Safe Motherhood (Bangladesh Journal of Bioethics, 2015)
Safe Motherhood is not only a Reproductive Right but also a basic human right. Provision of Safe Motherhood services like skilled attendants at birth reduces maternal deaths and morbidities. Bangladesh has reduced maternal deaths from 540/ 100,000 live births in the nineties to 194 in 2010. In a recent estimate by WHO, UNICEF, UNFPA, the World Bank and the United Nations Population Division, the Maternal Mortality Rate (MMR) has declined to 170 per 100,000 live births in Bangladesh.DOI: http://dx.doi.org/10.3329/bioethics.v5i3.21535 Bangladesh Journal of Bioethics 2014; 5(3):26-27